2009
DOI: 10.1002/pssa.200881593
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ordering in self‐organized (In,Ga)As quantum dot multilayer structures

Abstract: Molecular beam epitaxy (MBE) grown In0.5Ga0.5As/GaAs multilayer structures with quantum dots chains (QDs), obtained under different growth conditions, were investigated by high‐resolution X‐ray diffractometry (HRXRD) and AFM. It was determined that self‐organized epitaxial growth of In0.5Ga0.5As/GaAs can lead to the formation of three‐dimensional quantum‐dot crystals with triclinic (distorted cubic) unit cell. The mechanisms of QDs ordering in dependence on As flux are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Studies have shown that the form of the QD significantly affects the energy spectrum of quasiparticles [13]. Experimental work shows a difference from spherical [14][15][16], which ultimately affects the optical properties of materials. However, most of the work is devoted to spherically symmetric QDs due to its simpler solution.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the form of the QD significantly affects the energy spectrum of quasiparticles [13]. Experimental work shows a difference from spherical [14][15][16], which ultimately affects the optical properties of materials. However, most of the work is devoted to spherically symmetric QDs due to its simpler solution.…”
Section: Introductionmentioning
confidence: 99%